Advances in Cross-Cultural Decision Making Proceedings of the AHFE 2016 International Conference on Cross-Cultural Decision Making (CCDM), July 27-31,2016, Walt Disney World®, Florida, USA - Schatz, Sae; Hoffman, Mark (Advances in Intelligent Systems and Computing, 2017)
This book reports on the latest advances in understanding human cognition and its interplay with various cultural constructs, such as geographical, historical, sociological, and organizational cultures. It addresses researchers, scholars, and industry practitioners from diverse backgrounds, including sociology, linguistics, business, military science, psychology, human factors, neuroscience, and education. The book covers a wealth of topics, such as the analyses of historical events and intercultural competence, commercial applications of social-cultural science, the study of decision-making similarities (and differences) across cultures, Human, Social, Cultural Behavioral (HSCB) modeling and simulation technology, as well as social networks and studies on group communication. It also reports on real-world case studies relevant to cross-cultural decision making. The book aims at combining neurocognitive studies with studies from other relevant disciplines to develop a more holisticunderstanding of the decisions that people, groups, and societies make to improve the ability to forecast and plan for the future. The book is based on the AHFE 2016 International Conference on Cross-Cultural Decision Making (CCDM), held on July 27-31, 2016, in Walt Disney World®, Florida, USA.